A study to assess the effectiveness of structured teaching programme regarding knowledge and prevention of swine flu among patients at bollineni super specialty hospital in Nellore - Suja Shamili, G; Ramya kannan, K; Aruna, G; Prasad Naidu, M (International Journal of Nursing Research, 2023)
Background: Swine flu viruses do not normally infect humans. But, randomly, the human race got infected with swine flu. Most frequently, these cases occur in persons with direct exposure to pigs. Human-to-human transmission of swine flu can also occur. Aims: To assess knowledge regarding prevention of swine flu through pretest scores. To develop and implementation of structured teaching programme on knowledge and prevention of swine flu through post-test scores. Association between pretest level and post level of knowledge regarding prevention of swine flu with selected variables. Methodology: Sample collection is gathering information needed to address a research problem. Bollineni Super specialty Hospital of Nellore was selected for this study. Formal administrative approval was obtained from the Medical officer. Results: The demographic variables gender (0.3<3.84), family income (3.75<7.81) has not shown statistically significant association at p<0.05 level and hence it is lower than values. The other demographic variables age (15.19>7.81), education (8.02>7.81), and occupation (12.7>12.6) have shown significant association with the pre-test level of knowledge. The association of pre-test level of knowledge on prevention of swine flu with their demographic variables age (2.58<7.81), gender (0.36<3.84), education (4.91<7.81), occupation (7.6 <12.6), family income (2.81<7.81) has not shown statistically significant association at p<0.05 level. Conclusion: Currently nursing practice based on evidence-based practice. This research to equip the Medical health nurses to be an independent practitioner in various healthcare settings. In order to plan health education programme to improve knowledge of clients regarding knowledge and prevention of swine flu.C